Maximum Phonation Time and s/z Ratio in a Large Child Cohort - Mendes Tavares, Elaine Lara; Brasolotto, Alcione G.; Rodrigues, Sergio A. [UNESP]; Benito Pessin, Adriana Bueno; Garcia Martins, Regina Helena [UNESP] (Mosby-elsevier, 2012)
Aim. The purpose of this study was to provide normal values for maximum phonation time (MPT) and the s/z ratio by examining 1660 children aged 4-12 years and without vocal signs or symptoms.Methods. The technique was based on the sustained emission of the /a/ vowel and fricatives /s/ and /z/.Results. The average of the MPT in children of the different age groups was as follows: 6.09 seconds for the age group 4-6 years (males, 5.97; female, 6.21 seconds), 7.94 seconds for the age group 7-9 years (males, 8.07; females, 7.79 seconds), and 8.98 for the age group 10-12 years (males, 9.05; females, 8.92 seconds). The overall average for males was 7.78 and females 7.64 seconds. The s/z ratio was near 1.0 in most children but above 1.2 in 133 children and below 0.8 in 133 children.Conclusion. These values of MPT and s/z ratio can be used as normative in further pediatric studies.
Keywords: Maximum phonation time-s/z ratio; Child; Voice